Papogi the imaging of Philippine presidents (PCIJ, 2004)
This documentary shows the major archetypes of Philippine politics, the images and characters that aspring politicians have sought to duplicate and resurrect in subsequent elections. "Papogi" posits that the "marketing" of presidents and politicians in this country has been very much like the way movie studios have sold their actors: with flash and dash, and also myth-making and a careful tending of image and storyline.